Dumping Practices and Competition as Double-edged Sword: Indonesia Practices - Sukarmi, Sukarmi; Susanto, Fransiska Ayulistya (Indonesian Journal of International Law, 2023)
Dumping practices are typically related to business competition, namely predatory pricing. The issue under consideration is how the practice of dumping is viewed through the perspectives of business competition law and international trade law, as well as how the Indonesian Commission for the Supervision of Business Competition (KPPU) handles this issue. This article examines and analyzes the relationship between dumping behavior and business competition, as well as the authority with which institutions will handle predatory pricing caused by dumping behavior. The results of the analysis show that dumping is a violation of international trade law under the World Trade Organization (WTO). If the Indonesian Anti-Dumping Committee (KADI) discovers dumping practices, the party will be subject to sanctions in the form of Anti-Dumping Import Duty (BMAD). Aside from that, selling below market prices or carrying out predatory pricing will hinder fair competition from the perspective of competition law. Dumping practices benefit consumers in the short term but harm consumers and similar competing industries in the long term. If the aim is to eliminate competitors, of course, this is unhealthy competition and falls under the supervision and authority of KPPU to enforce the law. This article only focusses on the when the dumping practices can become the predatory pricing on competition law perspective and who will handle the case.